Between Resurrection and Insurrection: Jesus and the "Deconstruction of Monotheism" in "Von Der Zärtlichkeit" by Navid Kermani and "Ich, Jesus Von Nazareth" by Said - Twist, Joseph (Religion & literature, 2017)
The work of German-Iranian writers Navid Kermani and SAID points beyond the divisiveness of current debates surrounding Islam in Germany toward a non-identitarian spirituality. Despite their differences, Kermani's "Von der Zartlichkeit" (Of Tenderness) from the short-story collection Vierzig Leben (Forty Lives, 2004) and SAID's "ich, jesus von nazareth" (i, jesus of nazareth) from the short-story and essay collection Das Niemandsland is unseres: West-dstliche Betrcichtungen (The No-Man's-Land is Ours: West-eastern Observations, 2010) invite comparison because they share a deconstructive engagement with the figure of Jesus. Although "Von der Zartlichkeit" evokes a fleeting sense of the divine in withdrawal through allusions to Jesus's resurrection and "ich, jesus von nazareth" is the monologue of a socially radical Jesus whose spiritual significance lies in his actions, both ultimately constitute a rejection of monotheism's transcendent meaning-making. This less divisive concept of the divine can be illuminated byJean-Luc Nancy's philosophical writing on the concept of the "deconstruction of monotheism." In this regard, Nancy argues that in order to get beneath monotheism's need for a transcendental organizing principle, something that Nancy views as inherendy coercive, what is needed is an understanding of the divine as being located in the alterity of the material world. Hence, although these authors do draw upon understandings of Jesus from Christian and Islamic perspectives, their writing goes beyond dialogical attempts to harmonize the two religions by destabilising the dualist basis of monotheism itself.